Living on the slopes: entrepreneurial preparedness in a context under continuous threat - Muñoz, Pablo; Kimmitt, Jonathan; Kibler, Ewald; Farny, Steffen (Entrepreneurship and regional development, 2019)
In this paper, we examine how entrepreneurs living in communities under continuous threat prepare themselves to continue with their enterprising activities or engage in new ones after the expected crisis occurs. Most of the crisis literature on disasters and entrepreneurship focuses on aftermath responses, but the antecedents of such entrepreneurial behaviour and its connection to past and future crises remains largely unexplored. Based on a two-stage exploratory study pre and post the Calbuco Volcano eruptions in 2015 and 2016 in Chile, we introduce the notion of entrepreneurial preparedness in a context of continuous threat and elaborate on its four central attributes: anchored reflectiveness, situated experience, breaking through, and reaching out. Subsequently, our work develops a refined understanding of pre and post-disaster entrepreneurship and offers a novel base for theorizing on the relationship between entrepreneurial preparedness in contexts of continuous threat.